Studies on the Peel Oil from Two Varieties of Banana (Bangladesh Journal of Scientific and Industrial Research, 2011)
Composition of fatty oil in two different varieties of banana peels Mausa Cavendis (sagar kola) and Mausa Sapientum (savrie kola) was determined. Percent fatty oil content was found as 7.5 in savrie and 10 in Sagar peels. Unsaponifiable matter, Iodine value, free fatty acid contents and Saponification value were also determined for both the samples. It was observed that the linoleate content (2.74) in sagar variety is slightly higher than savrie variety (2.41), but the palmitate contents were found as 12.55 and 13.86, stearate contents 2.62 and 4.57 in Sagar and Savrie variety respectively. Key words: Oil; Saponification value; Iodine value; Banana; Peel DOI: 10.3329/bjsir.v45i4.7387 Bangladesh J. Sci. Ind. Res. 45(4), 393-396, 2010